Revealing performance factors for supply chain sustainability: A systematic literature review from a social capital perspective - Dias, Gustavo Picanço; Silva, Minelle (Brazilian Journal of Operations & Production Management, 2021)
Goal: The supply chain sustainability (SCS) literature is missing studies that specifically analyse factors that impact sustainability performance in supply chains, according to specific theoretical backgrounds. Within this context, this paper aims to understand how and why social capital theory (SCT) can inspire SCS studies and practice. In doing so, two research questions are addressed: (1) How has the SCS literature evolved in its application of the social capital theory?, and (2) What are the main sustainability performance factors studied in SCS?. Design / Methodology / Approach: A systematic literature review was developed. Data were collected from 12 years (2008–2019) in two databases (i.e. EBSCO and Web of Science) and a total of 56 articles were selected and analysed through deductive and inductive content analysis. Results: The analysis revealed 24 performance factors that influence SCS research throughout the three sustainability dimensions (i.e. economic, environmental and social). We found that social capital makes a significant conceptual contribution to understanding how the supply chain practices (i.e. cooperation, coordination, collaboration, resource exchanges and information sharing) explain how relationships are formed and interrelated to improve SCS performance. Limitations of the investigation: The use of two databases may present limited results, which may have resulted in missing publications. Practical implications: By recognising the performance factor for SCS, managers can identify their supply chain practices and increase their strategies within the relationship. Originality / Value: By revealing the performance factors that can increase SCS, this paper reinforce how powerful SCT is to explain SCS performance.